Waiting for the Stop Sign to Turn Green: Contemporary Issues on Drug and Alcohol Impaired Driving Policy - Stringer, Richard J. (American journal of criminal justice, 2022)
Impaired driving has been a considerable social problem in the U.S. for decades, but efforts to reduce it have stalled after the initial reductions in the 1980’s. As a result, legislators continue to develop more polices aimed at deterring impaired driving. Although alcohol has historically been the focus of these efforts, recently there has been increased concern about marijuana impaired driving policies as well. However, alcohol and marijuana impaired driving differ in many ways. This paper explores the costs and benefits of new zero-tolerance policies such as the reduction of the per-se Blood Alcohol Concentration (BAC) level from .08 to .05 for alcohol and the establishment of similar per-se limits for marijuana. These policies are not based on actual impairment and reflect a net widening effect that will criminalize unimpaired drivers, divert criminal justice resources away from the most problematic impaired drivers, and will have little impact on impaired driving crashes. As such, they have the potential to do more harm than good.